Delineation atlas of the Circle of Willis and the large intracranial arteries for evaluation of doses to neurovascular structures in pediatric brain tumor patients treated with radiation therapy. (2nd November 2021) - Toussaint, L.; Peters, S.; Mikkelsen, R.; Karabegovic, S.; Bäumer, C.; Muren, L. P.; Tram-Henriksen, L.; Høyer, M.; Lassen-Ramshad, Y.; Timmermann, B.
Abstract: Background: Survivors of pediatric brain tumors are susceptible to neurovascular disease after radiotherapy, with dose to the chiasm or Circle of Willis (CW) as risk factors. The aims of this study were to develop a delineation atlas of neurovascular structures, to investigate the doses to these structures in relation to tumor location and to investigate potential dose surrogates for the CW dose. Material and methods: An atlas of the CW, the large intracranial arteries and the suprasellar cistern (SC) was developed and validated. Thirty proton plans from previously treated pediatric brain tumor patients were retrieved and grouped according to tumor site: 10 central, 10 lateralized, and 10 posterior fossa tumors. Based on the atlas, neurovascular structures were delineated and dose metrics (mean dose ( D mean ) and maximal dose ( D max )) to these structures and the already delineated chiasm were evaluated. The agreement between dose metrics to the CW vs. chiasm/SC was investigated. The minimal Hausdorff distance (HDmin ) between the target and SC was correlated with the SC D mean . Results: The median D mean / D max to the CW were 53 Gy(RBE)/55 Gy(RBE) in the central tumors, 18 Gy(RBE)/25 Gy(RBE) in the lateralized tumors and 30 Gy(RBE)/49 Gy(RBE) in the posterior fossa tumors. There was a good agreement between the D max / D mean to the CW and the SC for all cases ( R 2 =0.99), while in the posterior fossa group, the CW D max was underestimated when using the chiasm as surrogate ( R 2 =0.76). Across all patients, cases with HDmin < 10 mm between the target and the SC received the highest SC D mean . Conclusion: The pattern of dose to neurovascular structures varied with the tumor location. For all locations, SC doses could be used as a surrogate for CW doses. A minimal distance larger than 10 mm between the target and the SC indicated a potential for neurovascular dose sparing.